Can Digital Transformation and Governance Control Managerial Opportunistic Behavior in Earnings Management? - Yolanda, Venna; Aria Farah Mita (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2025)
This research investigates the relationship of Digital Transformation, Audit Quality, and Board Characteristics on Earnings Management in non-financial companies listed on the Indonesia Stock Exchange from 2018 to 2022. Analysing 1,440 observations from 228 companies using purposive sampling and fixed effects regression, the findings reveal that Digital Transformation enhances transparency and real-time information access, reducing opportunities for earnings management, consistent with the Resource-Based View theory. High Audit Quality mitigates conflicts between managers and shareholders, aligning with agency theory. However, Board Characteristics, including size, independence, and meeting frequency, show no significant impact on earnings management, as most companies in the sample only comply with the minimum requirements of established corporate governance regulations, leading to homogeneity in board characteristics. This research provides a new perspective on the rarely researched relationship between earnings management and digital transformation, emphasising its implications for improving corporate governance in emerging markets.